1975
DOI: 10.3109/00952997509002740
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Testosterone Levels in Healthy Male Marijuana Smokers

Abstract: Plasma testosterone, FSH, and LH levels were obtained from 25 healthy consecutive heterosexual male mauijuana smoking university students. All values were within the range of normal and the means did not differ significantly from those of 13 normal controls. These data suggest that the casual marijuana smoker (at least one time weekly with an average of 5.1 joints per week) may have plasma testosterone levels which are normal for the time of day and the laboratory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…The effect of marijuana smoking has no significant effect on gonadotropin or testosterone levels (187). Excessive alcohol consumption has toxic effects on hepatocytes and leads to hypothalamic dysfunction associated with lower testosterone levels.…”
Section: Influence Of Recreational Drugs On Testosterone Levelsmentioning
confidence: 99%
“…The effect of marijuana smoking has no significant effect on gonadotropin or testosterone levels (187). Excessive alcohol consumption has toxic effects on hepatocytes and leads to hypothalamic dysfunction associated with lower testosterone levels.…”
Section: Influence Of Recreational Drugs On Testosterone Levelsmentioning
confidence: 99%
“…Marijuana use has been reported to lead to a decrease in sperm density and motility as well as to an increase in the number of sperm with abnormal morphology [20,38,56,73]. However, controversy exists as to the etiology of the spermatogenic dysfunction.…”
Section: Marijuanamentioning
confidence: 99%
“…However, controversy exists as to the etiology of the spermatogenic dysfunction. Some investigators have found decreased testosterone and gonadotropin levels in association with marijuana use [56], whereas others have observed normal gonadotropin levels in marijuana users [20,38]. Although the etiology is unclear, marijuana causes spermatogenic dysfunction and its use is a preventable cause of male infertility.…”
Section: Marijuanamentioning
confidence: 99%
“…The proposed mechanism is endocannabinoid signaling via receptors in the hypothalamus inhibiting GABA release, which in turn diminishes GnRH release with consequently lower LH levels (Farkas et al, 2010). However, others have failed to replicate these findings (Cushman, 1975;Wall et al, 1978). The earliest studies from the 1970s found that chronic cannabis consumption significantly lowered plasma testosterone levels in a dosedependent fashion (Kolodny et al, 1974).…”
Section: Cannabis and The Hypothalamic-pituitary-gonadal Axismentioning
confidence: 99%